The Importance of English Practice to Overcome the Students of Muhammadiyah Pringsewu Difficulty in Learning English - Siswoyo Siswoyo (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2023)
Learning English as a foreign language attracts many problems. This research investigates the students’ difficulties, factors affecting the difficulties, and the students' solutions to learning the English language. This research used a qualitative approach. The respondents of this research are fifteen students of the English Education Study Program The respondents were chosen purposively. The researcher used content analysis to analyze the data. The data were collected through a questionnaire distributed through Google form to make the respondents free to answer the questions in the Google form. This research showed that students had problems identifying vowels and consonant sounds, forming the affixation, and making nominal and verbal sentences. The factors that affect the students’ problems are the environment and lack of hard effort. The students had to practice listening to English sounds and speaking the English sounds in vowels and consonants to solve their problems in English learning.